A simple method for the quantification of diclofenac potassium in oral suspension by high-performance liquid chromatography with UV-detection (Brazilian Journal of Pharmaceutical Sciences, 2013)
A rapid, simple and low cost method was developed to determine diclofenac potassium (DP) in oral suspension, using a reverse-phase column (C8, 150 mm x 4.6 mm, 5 µm), mobile phase containing methanol/buffer phosphate (70:30 v/v, pH 2.5), at a flow rate of 1.0 mL/min, isocratic method, and ultraviolet detection at 275 nm. A linear response (r = 1.0000) was observed in the range of 10.0-50.0 µg/mL. Validation parameters such as linearity, specificity, precision, accuracy and robustness were evaluated. The method presented precision (repeatability: relative standard deviation = 1.21% and intermediate precision: between-analyst = 0.85%). The specificity of the assay was evaluated by exposure of diclofenac potassium under conditions of stress such as hydrolysis, photolysis, oxidation and high temperature. The method presented accuracy values between 98.28% and 101.95%. The results demonstrate the validity of the proposed method that allows determination of diclofenac potassium in oral suspension and may be used as an alternative method for routine analysis of this product in quality control.